Tension of Muslim-Christian Relations in Indonesia: The Case of Conversion and Celebrating Christmas - Zuly Qodir; Bilveer Singh (Al-Albab, 2021)
There are in the tense of Christian-Muslim relations in Indonesia since the time of the New Order until today. The issues in Christian-Muslim relations include conversion (of faith) with marriage and celebrating Christmas. These two issues are constantly associated with religious politics in Indonesia. The issues have kept tensions to reoccur, although according to Indonesian history, Christianity and Islam had jointly driven colonialists away and participated in founding the Unitary State of the Republic of Indonesia. In addition to theological affairs, the two issues relating to the tension of Christian-Muslim relationship have also impacted political and economic affairs. This article provides description of tension between Muslims and Christians in Indonesia in the case of conversion from Islam to Christian with marriage and celebrating Christmas in Muslim communities. The work concludes that in order to reduce tension between Christian and Muslim, all efforts to conduct theologia religionum dialogs should be sought, and social justice between Christians and Muslims should be created in the country. All of this is none other than a model of religious practices that have surpassed symbols. This is called passing over religious practices with new religious experiences.